A literature review on developing reading kiosk concept for nurturing reading habit among youth - Murad, Mirahida; Ibrahim, Mansor; Abdul Malek, Nurhayati; Abdullah, Fadzidah; Hashim, Khairusy Syakirin Has-Yun (KAED, IIUM, 2013)
Many activities and strategies had been implemented to nurture reading habit among Malaysian citizens. In a bid to boost reading programs, the Malaysian Government has outlined several approaches that are hoping to expand the reading culture among the citizens. However, statistics revealed by the National Library that Malaysian read 8 to 12 books per year. Compared to our nearest neighbor, Singaporeans read 30 books per year .People in Britain and Japan read an average of 20 books per year. So this means that, in the reading level perspective, Malaysia is far behind developed countries in the world. Empirical studies found that teenagers are reading fewer books in general and reading is declining as an activity among teenagers and they had a bad impression towards the library. Consequently, the library is used by teenagers mainly to study or do homework rather than to borrow items to read at leisure. De Medina (1976) found that reading which is outside school hours occurred when there was an allocated place to carry out reading activity. Having all these considerations, the main part of this research intention is to develop the concept of reading kiosks specifically to attract the teenagers in the study area. Based on the review undertaken, there is no study being conducted in assessing reading habit in relation to the built environment. Thereby, it is the interest of the research to investigate the relationship between reading habit and built environment, thus investigating the suitable design criteria of a reading place that can attract people coming for reading and finally proposing the concept of reading kiosk as a final output of the research. The participants of the research were the secondary school students at SMK Gombak Setia and SMK Bandar BaruSentul. This paper however, discusses the literature review on the reading habit, the approaches and the concept of the library being applied to promote reading activity among the citizens and also outline the research methodology that likely to partake. This study and review might be helpful in formulating the recommendations on the concept of reading kiosk as a final output of this research.